STUDY OF LEAD LEVEL IN AGRICULTURE SOIL, VEGETABLES AND IRRIGATED WATER NEARBY RIVER YAMUNA IN DELHI-NCR (Journal of Forensic Medicine & Toxicology, 2025)
Population expansion has resulted in greater urbanisation, industrialization, and agricultural operations to meet food demand, all of which generate environmental stress. Due to a shortage of fresh water, wastewater is used for irrigation, which is an important contributor of toxic metal. The present study looked at lead contents in soil and vegetable specimens from agricultural regions in Delhi-NCR. Although there have been several research on occupational heavy metal exposure, few have been undertaken on the widespread exposure to lead in study area. The purpose of this study is to assess the quantity of environmental consequences of heavy metals in wastewater, agricultural soil, and vegetables in the Delhi-NCR region. The sampling is done in two separate seasons that is before monsoon and after monsoon. In each season, 72 water and soil samples were taken, as well as 36 vegetable samples, from various places in the Delhi - NCR region. The acquired materials were further digested in a laboratory using the wet digestion process. Lead was detected in irrigated water, soil, and samples of vegetables using a device called an atomic absorption spectrophotometer. The average lead (Pb) content in water was 0.31 ± 0.01 mg/l. The smallest concentration was 0.05 mg/l, and the highest was 0.80 mg/l. The average content of lead (Pb) in agricultural
Keywords: agriculture soil; vegetable; water; lead; metal